The Effect of Internal Auditors' Knowledge and Professional Skepticism on the Artificial Intelligence Utilization - Bita Mashayekhi; Mohammad Reza Amrollahi (پژوهش‌های تجربی حسابداری)
This study explores how internal auditors' knowledge and professional skepticism influence their acceptance and use of artificial intelligence (AI) in auditing processes. As modern technologies advance, understanding the personal factors affecting AI adoption is critical for enhancing audit efficiency and accuracy. Employing a quantitative research approach with structural equation modeling (PLS-SEM), data were collected via a Likert-scale questionnaire from 244 internal auditors in the winter of 2024. The data were analyzed using the partial least squares method in SmartPLS software (version 4.09.05), with reliability and validity assessments confirming the structural model’s fit. The findings indicate that auditors’ knowledge has a significant positive impact on AI adoption, with more knowledgeable auditors showing a greater propensity to utilize AI. Contrary to expectations, professional skepticism does not significantly affect AI acceptance or use. These results suggest that auditors’ awareness and specialized training, rather than their level of professional skepticism, are the primary drivers of AI adoption. This study contributes to the literature on internal auditing and emerging technologies by underscoring the importance of enhancing auditors’ knowledge through targeted AI training programs and developing supportive technological infrastructures. Increased knowledge is expected to foster trust and acceptance of AI among internal auditors, promoting its broader use in audit processes and improving their quality and efficiency. These findings provide a foundation for future research on the impact of digital technologies on the internal audit profession